The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s00401-023-02604-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific MAPT gene expression is preserved in neuronal and glial tau cytopathologies in progressive supranuclear palsy

Abstract: Microtubule-associated protein tau (MAPT) aggregates in neurons, astrocytes and oligodendrocytes in a number of neurodegenerative diseases, including progressive supranuclear palsy (PSP). Tau is a target of therapy and the strategy includes either the elimination of pathological tau aggregates or reducing MAPT expression, and thus the amount of tau protein made to prevent its aggregation. Disease-associated tau affects brain regions in a sequential manner that includes cell-to-cell spreading. Involvement of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
3
12
0
Order By: Relevance
“…Such APP-FPN stabilization is demonstrated to be mediated by tau transport of APP to the cell membrane [42]. As tau expression is significantly higher in neurons [47], we may speculate that glia may have other mechanisms for maintaining iron homeostasis, which do not involve APP, making them relatively less vulnerable to Aβ-pathology-induced iron dysregulation. On the other hand, evidence suggests that astrocytes respond to extracellular Aβ pathology.…”
Section: Hypothesis 1 231 Iron Accumulation Is a Consequence Of Patho...mentioning
confidence: 95%
“…Such APP-FPN stabilization is demonstrated to be mediated by tau transport of APP to the cell membrane [42]. As tau expression is significantly higher in neurons [47], we may speculate that glia may have other mechanisms for maintaining iron homeostasis, which do not involve APP, making them relatively less vulnerable to Aβ-pathology-induced iron dysregulation. On the other hand, evidence suggests that astrocytes respond to extracellular Aβ pathology.…”
Section: Hypothesis 1 231 Iron Accumulation Is a Consequence Of Patho...mentioning
confidence: 95%
“…Recently, by using RNAscope imaging and single-nuclear RNAseq, Forrest and colleagues have shown the presence of the MAPT transcript in astrocytes (other than neurons and oligodendrocytes) both in patients affected by PSP and in control subjects [ 79 ]. Interestingly, the amount of MAPT in PSP patients was similar between healthy and tufted astrocytes [ 79 ].…”
Section: Origins Of α-Syn and Tau In Astrocytesmentioning
confidence: 99%
“…Recently, by using RNAscope imaging and single-nuclear RNAseq, Forrest and colleagues have shown the presence of the MAPT transcript in astrocytes (other than neurons and oligodendrocytes) both in patients affected by PSP and in control subjects [ 79 ]. Interestingly, the amount of MAPT in PSP patients was similar between healthy and tufted astrocytes [ 79 ]. Moreover, by using the same techniques, Fiock and colleagues found that the number of astrocytes expressing MAPT and the amount of MAPT expressed by each astrocyte is comparable between patients affected by AD, CBD, PSP and healthy controls [ 80 ].…”
Section: Origins Of α-Syn and Tau In Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodent models, astrocytic tau cannot propagate in the absence of neuronal tau expression [ 26 ], and human single-cell sequencing and RNA in situ hybridization data do not show an upregulation of tau expression in astrocytes from PSP patients [ 13 , 27 ]. Astrocytes will also readily take up recombinant tau fibrils or monomers in vitro [ 14 , 17 , 33 ].…”
Section: Introductionmentioning
confidence: 99%